Evaluasi Kinerja Komite Sekolah untuk Peningkatan Mutu Sekolah (Studi Kasus di SDN 2 Mandapajaya Kecamatan Cilebak Kabupaten Kuningan) - Aning Suhaeni; Maman Herman (Jurnal Edukasi (Ekonomi, Pendidikan dan Akuntansi), 2026)
This study addresses the limited in-depth research on the accountability and effectiveness of school committee performance in educational governance, particularly in supporting school quality improvement. It aims to describe and analyze the accountability and effectiveness of the school committee at SDN 2 Mandapajaya, Cilebak District, Kuningan Regency, the factors influencing its performance, and strategies for improvement. A descriptive qualitative case study design was employed, using interviews, observation, and documentation, with data analyzed through reduction, presentation, and conclusion drawing, validated by triangulation. Findings show that accountability remains predominantly administrative and not fully indicator-based, while effectiveness is reflected in program achievement and involvement in decision-making, though not yet systematically measured by outcomes. Influencing factors include member competence, internal communication, principal support, parental participation, and regulatory understanding. Improvement strategies include indicator-based planning, capacity development, monitoring and evaluation, and strengthening strategic partnerships.